2021
DOI: 10.1088/1755-1315/802/1/012045
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of lignite coal as heavy metal adsorbent in chemistry laboratory wastewater

Abstract: Wastewater from Chemistry Laboratory contains heavy metals which need treatment before being discharged into the environment. This study investigates the treatment of chemistry laboratory wastewater using activated carbon. The activated carbon was made from lignite coal with ZnCl2 activation and carbonization was carried out at a temperature of 500°C for 2 hours. The highest iodine number is 1529.20 mg/g on activated carbon with a grain size of 80 mesh of coal and a composition of 40% ZnCl2-60% coal. Adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In relatively shallow lakes, as a result of wind activity and resuspension of sediments, heavy metals are released into the water, and their circulation is quite intensive (Mrozińska and Bąkowska 2020 ). On the other hand, brown coal is very effective as an adsorbent material (Suliestyah et al 2021 ). On the surface of lignite, the adsorption process causes the binding of molecules, ions, or atoms of pollutants and heavy metal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In relatively shallow lakes, as a result of wind activity and resuspension of sediments, heavy metals are released into the water, and their circulation is quite intensive (Mrozińska and Bąkowska 2020 ). On the other hand, brown coal is very effective as an adsorbent material (Suliestyah et al 2021 ). On the surface of lignite, the adsorption process causes the binding of molecules, ions, or atoms of pollutants and heavy metal compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Lignite is rich in aromatic benzene ring and functional group-like petroleum structures, such as aliphatic hydrocarbons, aromatic hydrocarbons, carbon and oxygen branched chain 14 . These functional groups can undergo chemical reactions such as ion exchange, coordination and complexation with metal ions to achieve the adsorption effect 15 . Bao et al 16 showed that the removal efficiency of Cu 2+ by lignite reached 67.84 mg/g.…”
Section: Introductionmentioning
confidence: 99%